СЕЛЬСКОЕ НАСЕЛЕНИЕ КАРАКАЛПАКСТАНА В ГОДЫ ВТОРОЙ МИРОВОЙ ВОЙНЫ: МОБИЛИЗАЦИЯ И ТРУДОВОЙ ВКЛАД - Абдукаримов, А.А. (SCIENCE and SOCIETY, 2025)
The article examines the situation of the rural population of Karakalpakstan during the Second World War. Based on archival materials and published sources, the study analyzes mobilization processes, agricultural transformations, and the labor contribution of peasants to supporting the front and the home front. Special attention is given to the involvement of women and youth in production activities as well as social assistance to evacuated citizens. The research highlights the regional specificities of Karakalpakstan’s wartime economy and assesses its role within the broader Soviet home front system.
Keywords: Second World War; Karakalpakstan; rural population; mobilization; labor contribution; agrarian policy; home front